Activists communication dynamics for mobilization of minority politics in europe - Teguh Luhuringbudi; Muhammad Din Syamsuddin; Sudarnoto Abdul Hakim (Association for Scientific Computing Electrical and Engineering (ASCEE), 2019)
This paper aims to proves that the diversity of minority attributes in a person becomes the main capital in winning direct political contestation through election; or indirectly through unilateral appointment. It is characterized by five Muslim politicians who are able to sit in political office with the capital of political biography, social biography, and or intellectual biography. This research uses three methods in the form of political biography, social biography, and intellectual biography. Political biography consists of opinions or thoughts expressed by David Hanlon (2015); and opinions or thoughts of Anastasia Astapova (2016). The social biography used in this study refers to the thought of Smiljka Tomanović (2012). The intellectual biography used in this study is based on the thoughts of Damián Omar Martínez (2013) and the thinking of Thomas Hylland Eriksen (2015). The study was limited to five Muslim politicians comprising Jilani Chowdhury (Mayor of London, 2012), Ahmed Aboutaleb (Mayor of Rotterdam, 2008), Muhammad Salique (Mayor of Tower Hamlets, London Raya, 2008-2009), Erion Veliaj (Mayor of Tirana, 2015 ), Sadiq Aman Khan (Mayor of London, 2016), and Hadia Tajik (Norwegian Minister of Culture, 2012). This study is limited to the study of European Muslim Politicians in the perspective of a major theme. This study is also limited during the study that took place in Europe in 2012 until 2016